Instalações elétricas: uma proposta para ensino da eletrodinâmica no 3º do ensino médio - Neves, Glauber Siqueira (2019)
In this paper we present a didactic sequence, aiming to teach Electrodynamic concepts to third year high school students, and in particular, those related to the electrical circuits of a residential electrical installation. The activities developed were based on Vygotsky's Socio-Historical theory and the product consists of a guide for the teacher, in which he will find not only the activities of the didactic sequence that we propose for the learning of these concepts, laws and properties, but also suggestions on how to organize classroom activities and how to act as a mediator during such activities. In addition, a model of a residential electrical installation built by the students with the guidance of the teacher with leftover materials is used, used as a facilitating pedagogical tool in the internalization of the concepts. As a data collection mechanism, a Pre and Post Test were used, containing 06 questions each. A qualitative analysis was carried out from the answers to the test questions, generating a test score to assess the individual performance of the students in the class. The proposed resources used contributed to the students' motivation and the promotion of learning some concepts of electrodynamics for the group of students of this State School.